Spectral studies of safranin-O in different surfactant solutions - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2003)
The interaction of Safranin-O (SO), a cationic dye, with various surfactants viz., anionics; Sodiumdodecylsulfate (SDS) and Sodiumdodecylsulfonate (SDSo), nonionics; polyoxyethylenesorbitanmonolaurate (Tween 20) and polyoxyethylenedodecylether (Brij 35), cationic; Dodecyltrimethylammoniumbromide (DTAB) and zwitterionic; Laurylsulfobetaine (LSB) was studied spectrophotometrically as a function of surfactant concentration ranging from premicellar to postmicellar region in aqueous media in the absence and presence of cosolvents. The binding constants (K-b) and fraction of bound SO to micelles (f), were calculated by means of Benesi-Hildebrand Equation. The binding tendency of SO to micelles followed the order as; Tween 20 > Brij 35 > SDS > SDSo > LSB. The presence of cosolvents. such as Methanol, Dimethylformamide (DMFA) and 1,4 Dioxan (DX) at various volume percentages, increased the CIVIC of both SDS and Tween 20 and at a certain concentration totally inhibited the micellization. The bindina of SO to micelles decreased as the concentration of the cosolvents increased. This inhibitory effect of cosolvents on binding of SO to micelles followed the order as; Methanol > DMFA > DX. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: dye-surfactant interaction; cosolvent; safranin-O; cationic dye; binding constant; CRITICAL MICELLE CONCENTRATION; AMPHIPHILIC HEMICYANINE DYES; PRINCIPAL COMPONENT ANALYSIS; DODECYL-SULFATE MICELLES; COOMASSIE BRILLIANT BLUE; SHORT-CHAIN ALCOHOLS; HYDROPHOBIC INTERACTION; CATIONIC SURFACTANT; ANIONIC SURFACTANT; AQUEOUS-SOLUTIONS